TEG's Utility to Detect Hypercoagulability in Adult Patients at Post-Cardiac Surgery Using Cardiopulmonary Bypass in ICU - Hildegardis Dyna Dumilah; Hartono Kahar; Arifoel Hajat; Philia Setiawan; Heroe Soebroto (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
The use of Cardiopulmonary Bypass (CPB) in adult patients of cardiac surgery disrupts the coagulation system. The most common complication of the coagulation system is bleeding; however, that does not rule out the possibility of a dangerous hypercoagulation condition. A quick and precise coagulation test can provide clues for clinicians to predict future hemostatic disorders or determine interventional therapy. aPTT and PT are standard laboratory tests, which are limited to detect a deficiency of coagulation factors. Thromboelastography (TEG) test (R time, K time, Î± angle, MA, and LY30) provides an overview of the entire coagulation and fibrinolysis process with faster results. A 2.7 mL citrate blood sample was taken and tested in a TEG®5000 device, then centrifuged. The plasma was then tested for aPTT and PT using the Sysmex CS-2100i device. Bleeding volume was measured from chest drain 1-2 hours in the ICU after chest closure in the operating room. Bleeding criteria were as follows: > 1.5 mL/kg/hour for 6 hours consecutively in 24 hours or > 100 mL/hour. The results showed 30 patients with no clinically significant bleeding. A significant correlation was found between PT and bleeding volume at IV hour (p=0.008, r= 0.472). There was no correlation between aPTT and TEG (R time, K time, Î± angle, MA, and LY30) with the bleeding volume at I, II, III, and IV hours. There was a hypercoagulation indication of the TEG test of 56.7%, which showed clinical importance for the patient. PT can be used to analyze changes in bleeding volume at IV hour and TEG is more superior to detect hypercoagulability of adult patients after cardiac surgery with CPB.